2012
DOI: 10.1016/j.ijgo.2011.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐dose vaginal misoprostol and single‐dose misoprostol plus oxytocin for termination of second‐trimester pregnancy

Abstract: The use of misoprostol with oxytocin, and multiple doses of misoprostol gave similar results for termination of pregnancy in the second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Zangeneh et al (22) compared two strategies utilizing misoprostol alone and in conjunction with concentrated oxytocin and discovered a more successful way to perform a clinical abortion in the second trimester. Misoprostol and oxytocin appear to be effective and appropriate methods of terminating the pregnancy in the second trimester, according to the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Zangeneh et al (22) compared two strategies utilizing misoprostol alone and in conjunction with concentrated oxytocin and discovered a more successful way to perform a clinical abortion in the second trimester. Misoprostol and oxytocin appear to be effective and appropriate methods of terminating the pregnancy in the second trimester, according to the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Zangeneh et al. () studied the use of vaginal misoprostol and vaginal misoprostol combined with intravenous oxytocin and found similar results in the duration from initiation of medications and birth in second trimester pregnancies. The authors recommend both drug regimens to facilitate induction and birth of a second trimester pregnancy, as women in this study experienced few side effects and a short interval between initiation of the medication and vaginal birth (Zangeneh et al., ).…”
Section: Nursing Care During the Intrapartum Periodmentioning
confidence: 91%
“…Dosing regimen of misoprostol for IOL still represents a challenge; Zangeneh et al (13) found combined use of misoprostol with oxytocin gave similar results to the use of multiple doses of misoprostol for 2 nd trimester termination of pregnancy. However, for IOL misoprostol dose-adjustment was not fully evaluated, thus the current study targets to evaluate dose-related outcome of IOL in multipara women so as to determine the appropriate dose for getting trial success defined as having vaginal delivery (VD) within 24-hr induction-to-delivery (ITD) interval.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%